2011
DOI: 10.7763/ijesd.2011.v2.149
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties of Maize Residues under Application of Organic and Inorganic Nutrient Sources

Abstract: -Although the use of crop residues to enhance soil fertility has been suggested over the years, little is known about the nutrient composition of these residues as affected by specific nutrient management strategies. A study was conducted at the Soil Research Institute, Kwadaso, Ghana to examine the chemical properties of maize residues after application of different nutrient sources. The study was a field experiment arranged in a randomized complete block design. The treatments considered were application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Therefore, due to havingthe significant effect of minerals on livestock productivity should be analyzing the mineral contests of the crop residue at a time before feeding for our animals. [33][34][35][36][37][38]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to havingthe significant effect of minerals on livestock productivity should be analyzing the mineral contests of the crop residue at a time before feeding for our animals. [33][34][35][36][37][38]…”
Section: Discussionmentioning
confidence: 99%
“…The substrate (rice husk) was analyzed before and after pretreatment for the following parameters using standard methods as described by Association of Official Analytical Chemists, AOAC (2005): pH of the substrate was determined using pH meter (Micro pH 2000) on 1:2.5 (w/v) substrate/water mixture. Moisture content was determined by oven dry weight method at 105 0 C for 3 hours while ash content was determined by ashing the substrate in a furnace at 550 0 C. Crude protein content of the substrate was determined using the macro Kjeldah method (AOAC, 2005;Logah, 2011). Lignin and alpha cellulose contents were determined gravimetrically (AOAC, 2005;Anwar et al, 2012); Hemicellulose estimation was done by NaOH treatment and refluxing at 80 o C for 4 hours; Cellulose estimation was done by subtracting from 100%, the sum of hemicelluloses, lignin, ash, alpha cellulose and moisture while hollocellulose was estimated by the sum of cellulose and hemicelluloses (AOAC, 2005) Bioethanol Production: The processes for bioethanol production were pretreatment, hydrolysis, fermentation and fractional distillation (Oyeleke et al, 2012 andOnwuakor et al 2017).…”
Section: Physicochemical Analysis Of Rice Huskmentioning
confidence: 99%
“…Over 50% of these nutrients are available in the large amounts of rice straw produced in the Northern region. Logah [51] indicated that maize straw amended with chemical fertilizer could increase the nitrogen and phosphorous nutrient level of maize straw with lower polyphenol, which will translate into increasing the productivity of crops. Quartey and Chýlková [24] equally emphasized that straw is being used as a fertilizer to help in the productivity of crops in Ghana.…”
Section: Feed For Livestockmentioning
confidence: 99%